THE SPECIFICS OF STUDENTS' THINKING IN PRIMARY SCHOOL - Zaripova Muslima Kurbanovna (American Journals, 2025)
The article argues that the acquisition of knowledge by a child in the process of teaching younger students may be the result of a different type of thinking, which is called empirical. At the same time, it is reported about the acquisition of knowledge based on empirical thinking, comparing the external similarity of objects and phenomena in the environment, and identifying common features.
Keywords: Empirical, logic, thinking, didactic game, student, learning, mental attitude.